PENGAWASAN LIMBAH SAWIT OLEH DINAS LINGKUNGAN HIDUP KABUPATEN KUANTAN SINGINGI (Studi Kasus Pencemaran Sungai Bawang Oleh PT. Sun) - Asmara Indriyani; Abdul Sadad (Jurnal Relasi Publik, 2023)
Kuantan Singingi Regency is one of the regencies in Riau Province which is growing rapidly in recent years, one of which is in the field of oil palm plantations. However, due to the rapid establishment of oil palm companies, it causes a lot of palm oil waste disposal caused by the disposal of these companies. The purpose of this study was to determine the supervision of palm oil waste by the Environmental Service of Kuantan Singingi Regency (Case Study: Sungai Bawang Pollution). Then to find out the inhibiting factors in the implementation of waste control in the Bawang River, Singingi Hilir District, Kuantan Singingi Regency. The monitoring activities that have been carried out are the activities of controlling palm oil waste with a percentage exceeding the quality standard, the activities carried out by the Environmental Service are not yet maximal so that violations pass the quality standards, and the lack of firmness in giving sanctions to companies is a phenomenon found. This type of research is qualitative research with a descriptive case study approach. The collection of data obtained, both primary data and secondary data were collected through interviews, observations and documentation and then analyzed so that conclusions can be drawn from existing research problems. The results of this study found that the supervision of the environmental service in the supervision of palm oil waste has not been carried out optimally, this is caused by several inhibiting factors, namely the ability of human resources, funds and infrastructure and company behavior